Bud Rots of Palm - Monica L. Elliott (EDIS, 2019)
There are many pathogens that can cause bud rots of palm in Florida. The most common one is Phytophthora palmivora, followed by Thielaviopsis paradoxa and bacteria. Symptoms of bud rot are similar no matter which pathogen causes the disease. This document is PP-220, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.